Third generation cephalosporin resistance in clinical non-typhoidal Salmonella enterica in Germany and emergence of blaCTX-M-harbouring pESI plasmids. Issue 10 (25th October 2021) - Pietsch, Michael; Simon, Sandra; Meinen, Anika; Trost, Eva; Banerji, Sangeeta; Pfeifer, Yvonne; Flieger, Antje
Abstract : Non-typhoidal Salmonella enterica is an important gastrointestinal pathogen causing a considerable burden of disease. Resistance to third generation cephalosporins poses a serious threat for treatment of severe infections. In this study occurrence, phylogenetic relationship, and mechanisms of third generation cephalosporin resistance were investigated for clinical non-typhoidal S. enterica isolates in Germany. From 2017 to 2019, we detected 168 unique clinical S. enterica isolates with phenotypic resistance to third generation cephalosporins in a nation-wide surveillance. Compared to previous years, we observed a significant ( P =0.0002) and consistent increase in resistant isolates from 0.41 % in 2005 to 1.71 % in 2019. In total, 34 different serovars were identified, most often S . Infantis ( n =41; 24.4 %), S . Typhimurium ( n =27; 16.1 %), S . Kentucky ( n =21; 12.5 %), and S . Derby ( n =17; 10.1 %). Whole genome analyses revealed extended-spectrum β-lactamase (ESBL) genes as main cause for third generation cephalosporin resistance, and most prevalent were bla CTX-M-1 ( n =55), bla CTX-M-14 ( n =25), and bla CTX-M-65 ( n =23). There was no strict correlation between serovar, phylogenetic lineage, and ESBL type but some serovar/ESBL gene combinations were detected frequently, such as bla CTX-M-1 and bla CTX-M-65 in S . Infantis or bla CTX-M-14b in S . Kentucky. The ESBL genes were mainly located on plasmids, including IncI, IncA/C variants, emerging pESI variants, and a novel bla CTX-M-1 harbouring plasmid. We conclude that third generation cephalosporin resistance is on the rise among clinical S. enterica isolates in Germany, and occurrence in various S. enterica serovars is most probably due to multiple acquisition events of plasmids.